The Influence of Price and Product Quality on the Purchase Decision of iPhone Brand Smartphones Among Students - Nurwidyanti, Ferisca; Gusti , Rahma Welda (International Journal of Law Policy and Governance, 2025)
Purpose –To determine the influence of price and product quality on the purchasing decision of iPhone brand smartphones among management students at the Pekanbaru Master Business Technology Institute, totaling 95 respondents..Methodology/approach –The variables examined in this study were price and product quality on purchasing decisions. Data analysis used multiple linear regression methods, including validity, reliability, normality, multiple linear regression, t-test, f-test, and coefficient of determination (R2) using SPSS. This test was conducted to determine the influence of the independent and dependent variables.Findings –The results of the study show that partially and simultaneously there is an influence between the variables of price and product quality on students' purchasing decisions.Novelty/value – There is a tendency for students of the Master of Business Technology Institute to prefer purchasing iPhone products because of their brand and quality.